Pengembangan Bahan Ajar Berbentuk Poster pada Tema Energi dan Perubahannya pada Siswa Kelas III SD Negeri 102011 Sei Buluh - Diah Utami; Fata Ibnu Hajar (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to determine the process and analyze the feasibility of developing teaching materials in the form of posters on the theme of energy and its changes in third grade students of SD Negeri 102011 Sei Buluh. This research uses the ADDIE development model (Analyze, Design, Develop, Implementation and Evaluation) and the instruments used in this research are validation and needs questionnaire sheets. From the development process, a product is produced in the form of teaching materials in the form of posters that can be used in the learning process of the theme of energy and its changes. Then, the results of the feasibility of the material were obtained at 80% with "very good" criteria, then the feasibility of language obtained a value of 82% with "very good" criteria and the feasibility of design obtained a result of 89.3% with "very good" criteria. The results of the three feasibilities obtained an average of 83.7% with the criteria "very good". Based on the results of the feasibility of material, language and design, it can be concluded that the product that the researchers developed, namely teaching materials in the form of posters on the theme of energy and its changes in third grade students of SD Negeri 102011 Sei Buluh, is suitable for use in the learning process in class.